2011
DOI: 10.1259/bjr/14980811
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in the assessment of tumour grade in endometrial cancer

Abstract: Objective: Endometrial cancer is the most common gynaecological malignancy in developed countries. Histological grade and subtype are important prognostic factors obtained by pipelle biopsy. However, pipelle biopsy ''samples'' tissue and a high-grade component that requires more aggressive treatment may be missed. The purpose of the study was to assess the use of diffusion-weighted MRI (DW-MRI) in the assessment of tumour grade in endometrial lesions. we obtained a sensitivity, specificity, positive predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 34 publications
9
54
1
Order By: Relevance
“…This can be attributed to Type 1 cancers, which are oestrogen-sensitive and more common in a young age group. 4 The link between ADC value and tumour grade is consistent with a previous report by Tamai et al 12 from an Asian population, but not seen in another report by Bharwani et al 33 from a Western population. Indeed, this inconsistent observation can be attributed to different disease prevalence geographically.…”
Section: Discussionsupporting
confidence: 89%
“…This can be attributed to Type 1 cancers, which are oestrogen-sensitive and more common in a young age group. 4 The link between ADC value and tumour grade is consistent with a previous report by Tamai et al 12 from an Asian population, but not seen in another report by Bharwani et al 33 from a Western population. Indeed, this inconsistent observation can be attributed to different disease prevalence geographically.…”
Section: Discussionsupporting
confidence: 89%
“…Higher‐grade tumors generally have higher cellular density and therefore would be anticipated to show a lower ADC . However, most previous investigations have found no significant correlation between mean ADC and tumor grade . Tamai et al reported a significant difference between mean ADCs of grade 1 and grade 3 tumors, but considerable overlap was present in that study and precise estimation of histological grade based on mean ADC still seems difficult.…”
Section: Discussionmentioning
confidence: 87%
“…Another study showed that although in comparison to benign endometrial pathology (e.g. benign polyps and hyperplasia) ADC values of endometrial cancer were significantly lower [29], no significant differences were detectable between different histological grades. These conflicting results might be explained due to the small sample sizes and necessitate the use of larger, prospectively powered studies.…”
Section: Endometrial Cancermentioning
confidence: 97%